2019
DOI: 10.12968/pnur.2019.30.12.596
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and health inequalities: the role of the practice nurse

Abstract: As the patient populations continue to diversify, Vanessa Healsip and Claire Nadaf explore the health inequalities that certain patient groups are experiencing. For practice nurses, cultural competence is a key skill in improving healthcare for all patients General practice is becoming increasingly diverse due to a changing patient base and political climate, which impacts on the practice nurse's role. Over the past decade, there has been an increase in the number of foreign-born individuals living in the UK,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Studying health inequity in older populations is important as it undermines healthy ageing (WHO 2017 ). However, most studies on inequity in the healthcare setting have focused on providing recommendations on how to tackle it with no specific focus on the hospital discharge process (Alvarez-Dardet and Ruiz 2001 ; Healsip and Nadaf 2019 ; Woodward and Kawachi 2001 ). Recent studies on inequity in the hospital discharge have shown that language barriers (Malevanchik et al 2021 ) and lack of policy tailored to patients with no fixed address (Jenkinson et al 2020 ) contribute to inappropriate discharges and health inequity.…”
Section: Introductionmentioning
confidence: 99%
“…Studying health inequity in older populations is important as it undermines healthy ageing (WHO 2017 ). However, most studies on inequity in the healthcare setting have focused on providing recommendations on how to tackle it with no specific focus on the hospital discharge process (Alvarez-Dardet and Ruiz 2001 ; Healsip and Nadaf 2019 ; Woodward and Kawachi 2001 ). Recent studies on inequity in the hospital discharge have shown that language barriers (Malevanchik et al 2021 ) and lack of policy tailored to patients with no fixed address (Jenkinson et al 2020 ) contribute to inappropriate discharges and health inequity.…”
Section: Introductionmentioning
confidence: 99%
“…Promoting health and wellbeing is a fundamental part of every nurse's role (Nursing Midwifery Council 2018). Practice nurses are ideally placed within local communities to have a significant impact on addressing health inequities (Heaslip and Nadaf 2019). However, to achieve this they need to understand the many factors that lead to certain groups having poorer health outcomes.…”
Section: Introductionmentioning
confidence: 99%